Chronic brain histamine depletion in adult mice induced depression-like behaviours and impaired sleep-wake cycle. (15th September 2020) - Yamada, Yo; Yoshikawa, Takeo; Naganuma, Fumito; Kikkawa, Takako; Osumi, Noriko; Yanai, Kazuhiko
Abstract: Histamine acts as a neurotransmitter to regulate various physiological processes. Brain histamine is synthesized from an essential amino acid histidine in a reaction catalysed by histidine decarboxylase (Hdc). Hdc-positive neurons exist mainly in the tuberomammillary nucleus (TMN) of the posterior hypothalamus and project their axons to the entire brain. Recent studies have reported that a chronic decrease in histamine levels in the adult human brain was observed in several neurological disorders. However, it is poorly understood whether lower histamine levels play a causative role in those disorders. In the present study, we induced chronic histamine deficiency in the brains of adult mice to allow direct interpretation of the relationship between an impaired histaminergic nervous system and the resultant phenotype. To induce chronic brain histamine deficiency starting in adulthood, adeno-associated virus expressing Cre recombinase was microinjected into the TMN of Hdc flox mice (cKO mice) at the age of 8 weeks. Immunohistochemical analysis showed expression of Cre recombinase in the TMN of cKO mice. The reduction of histamine contents with the decreased Hdc expression in cKO brain was also confirmed. Behavioural studies revealed that chronic histamine depletion in cKO mice induced depression-like behaviour, decreased locomotor activity in the home cage, and impaired aversive memory. Sleep analysis showed that cKO mice exhibited a decrease in wakefulness and increase in non-rapid eye movement sleep throughout the day. Taken together, this study clearly demonstrates that chronic histamine depletion in the adult mouse brain plays a causative role in brain dysfunction. Highlights: Causal links between the histamine system and brain disorders are unknown. We induced chronic histamine depletion in cKO mice using adeno-associated viruses. cKO showed depression-like behaviour, impaired memory, and low locomotor activity. Sleep analysis showed decreased wakefulness and increased NREM sleep in cKO. An abnormal histaminergic system in adults could underlie brain dysfunction.